Effectiveness of Local Legend-Based Audio-Visual Media on Improving Elementary School Students' Literacy in Rural Areas - Ajeng Ratna Permana; Agus Hamdani; Deasy Aditya Damayanti; Yustika Nur Fajriah (Papanda Publisher, 2026)
Rural elementary students in Indonesia face persistent literacy barriers compounded by limited access to culturally relevant instructional materials. This study investigates the effectiveness of local legend-based audio-visual media in reinforcing literacy skills among primary school students in rural areas. A descriptive mixed-methods design was employed, involving a purposive sample of 40 Grade IV and V students and four classroom teachers at two elementary schools in Blubur Limbangan District, Garut Regency. Data were collected through a validated literacy achievement test (CVR = 0.87; α = 0.84), participatory observation across eight learning sessions, and semi-structured teacher interviews. Quantitative data were analyzed descriptively; qualitative data were analyzed using the interactive model of Miles, Huberman, and Saldaña (2014). Results showed that 42.5% of students achieved